TOWARDS THE EROTIC PHENOMENON: A PROLEGOMENA FOR CONTEMPORARY EROTOLOGY (Philological Studies, 2019)
The goal of this paper is to present the basic positions of erotology that treats erotic as a true phenomenon of the humain existence. Despite of the traditional understanding of erotic as a vulgar manifestation of bodylines and bestial sexual desire, contemporary erotology considers erotic to be a form of transcendence, comprehensive human aspiration of a restrained being of finality to the infinity. Trying to build a system of multidisciplinary argumentation, the author counts with the fundamental overcoming of the narrow apprehension of the eroticism in the domain of genitality and sexual desire, and its understanding, instead, in the context of the fundamental structures rooted human being as a whole, determine, in a specific way, its behavior and its cognitive abilities and powers.
Keywords: eroticism, erotology, phenomenology